Strategies and challenges of internationalisation in BRIC-countries: Empirical results from the German agribusiness - Matthias Heyder; Ludwig Theuvsen (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
The objective of this paper is to identify the strategies and instruments that agribusiness companies currently use to cope with the globalisation of agricultural markets. This aim is achieved by means of presenting the empirical results of an online and telephone survey that was undertaken between April and August 2010 with the participation of 113 German agribusiness firms. The majority of respondents expect that the importance of the markets in the BRIC countries will increase remarkably in the future. For developing international business activities, comparatively simple strategies such as direct and indirect exports via domestic and international traders are most widely used. This may be the result of challenges the agribusiness companies are facing in the context of handling international markets, especially in BRIC countries.
Keywords: Q13; L10; 330; agribusiness; internationalisation; firm strategy; BRIC